On the validity of the German version of the comprehensive psychopathological rating scale - Richter, Paul; Saß, Henning; Sauer, Heinrich (European archives of psychiatry and clinical neuroscience, 1990)
The construct validity of the German Version of the Comprehensive Psychopathological Rating Scale (CPRS) was investigated in a longitudinal study on 60 hospitalised RDC-schizoaffective patients. The validation included tests of hypotheses about means in cross-section and, in therapy, the course of schizoaffective psychoses. Thus, it is assumed that differences in diagnosis (RDC-schizodepressives versus RDC-schizomanics) are reflected by significantly higher scores on the respective subscales of the CPRS. Furthermore, the subscales of the CPRS should be sensitive to therapeutic change. In addition, correlations were tested using instruments of similar or different validity claim (Hamilton Depression Scale, Mania Rating Scale, Brief Psychiatric Rating Scale). All hypotheses about means could be confirmed. The convergent and discriminant validity of the CPRS is discussed on the basis of multiple-indicator matrices computed for each of the three points of measurement.
Gesehen am 29.01.2021